2012
DOI: 10.3354/meps09584
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of the intertidal goby Chaenogobius annularis associated with paleoenvironmental changes around the Japanese Archipelago

Abstract: We examined the phylogeography of the common Japanese intertidal goby Chaenogobius annularis using the mitochondrial cytochrome b gene, the NADH dehydrogenase subunit 2 gene, and the surrounding transfer RNA from 195 specimens collected in 27 localities around the Japanese Archipelago and the Korean Peninsula, and reconstructed the historical processes of its current distribution. In total, 169 unique haplotypes were obtained, and phylogenetic trees showed 2 genetically distinct lineages: the Pacific Ocean and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 54 publications
2
38
0
Order By: Relevance
“…, ; Kokita & Nohara ; Hirase et al . ). The low M‐ ratio values observed in most of the amphidromous form of ayu along the coast of the Sea of Japan (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…, ; Kokita & Nohara ; Hirase et al . ). The low M‐ ratio values observed in most of the amphidromous form of ayu along the coast of the Sea of Japan (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…A parent fish defends the eggs until the hatching of the larvae, and the larvae then drift along the shore, forming cohorts. We have previously undertaken a large‐scale study of genetic differentiation among populations of C. annularis , and have shown that this species consists of several geographical groups, of which the structure reflects the historical vicariance caused by environmental changes around the Japanese archipelago (Hirase et al in press). In addition, this study also revealed a high level of genetic differentiation within the geographical groups, suggesting the low dispersal ability of C. annularis.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of genetically distinct groups has also been reported for some shallow-water marine fish species in the northwestern Pacific: Chelon haematocheilus (Liu et al 2007), Ammodytes personatus (Han et al 2012), and Chaenogobius annularis (Hirase et al 2012). This demonstrates that isolation in the deep-sea basin is not the unique cause of genetic breaks among marine fish species in this area.…”
Section: Discussionmentioning
confidence: 99%